Associations between objectively measured sleep parameters and cognition in healthy older adults: A meta-analysis. (February 2023) - Qin, Shuo; Leong, Ruth L.F.; Ong, Ju Lynn; Chee, Michael W.L.
Abstract: Multiple studies have examined associations between sleep and cognition in older adults, but a majority of these depend on self-reports on sleep and utilize cognitive tests that assess overall cognitive function. The current meta-analysis involved 72 independent studies and sought to quantify associations between objectively measured sleep parameters and cognitive performance in healthy older adults. Both sleep macrostructure (e.g., sleep duration, continuity, and stages) and microstructure (e.g., slow wave activity and spindle activity) were evaluated. For macrostructure, lower restlessness at night was associated with better memory performance ( r = 0.43, p = 0.02), while lower sleep onset latency was associated with better executive functioning ( r = 0.28, p = 0.03). Greater relative amount of N2 and REM sleep, but not N3, positively correlated with cognitive performance. The association between microstructure and cognition in older adults was marginally significant. This relationship was moderated by age ( z = 0.07, p < 0.01), education ( z = 0.26, p = 0.03), and percentage of female participants ( z = 0.01, p < 0.01). The current meta-analysis emphasizes the importance of considering objective sleep measures to understand the relationship between sleep and cognition in healthy older adults. These results also form a base from which researchers using wearable sleep technology and measuring behavior through computerized testing tools can evaluate their findings.